The Teaching Profile of Matriculation College Science Teachers in Malaysia - Yakob, Nooraida; Ahmad Rashed, Rabiatul Adawiah (EDUCARE, 2010)
ABSTRACT: Teaching is an important process in order to produce a meaningful learning. As an intermediate program, every teacher in Matriculation College should be able to produce an effective teaching process, particularly in teaching Science which is full with abstract concepts. To achieve that, Science teachers need the teaching profile as a guidance to develop a flexible, creative, and innovative teaching process. As a result, the learning process will meet the studentsâ need and the objectives of twenty-first century education. Therefore, the purpose of this study is to identify the teaching profile and sub-profile patterns of matriculation Science teachers in Malaysia. For this purpose, 344 Science teachers from eight Matriculation Colleges were selected. Data was collected by using questionnaire as a main instrument. The finding showed that the professional knowledge and the professional attitudes dominate the profile patterns. While the sub-profile patterns dominated by pedagogical content knowledge and relationship among colleagues. It is also safe to say that the professionalism profile will be the ultimate key towards upgrading teachersâ quality, the quality of the teaching process as well as the quality of the product that is the students. This study suggests that the dominated profile and sub-profile show the matriculation teachersâ strength in teaching Science.Â Â Â KEY WORDS: Teaching profile, Science teacher, teacherâs knowledge, professional knowledge, professional practices, professional attitudes.Â Â About the Authors: Nooraida Yakob and Rabiatul Adawiah Ahmad Rashed are Lecturers at the School of Educational Studies USM (Universiti Sains Malaysia or Science University of Malaysia), Pulau Pinang, Malaysia. They can be contacted via e-mails at: nooraidaya@hotmail.com and r_adawiah@usm.myHow to cite this article? Yakob, Nooraida & Rabiatul Adawiah Ahmad Rashed. (2010). âThe Teaching Profile of Matriculation College Science Teachers in Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.3(1) August, pp.103-114. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (June 17, 2010); Revised (July 19, 2010); and Published (August 17, 2010).